Jews, Judaism, and success : how religion paved the way to modern Jewish achievement - Eisen, Robert, 1960- (University of Toronto Press, 2023)
"In Jews, Judaism, and Success, Robert Eisen attempts to solve a long-standing mystery that has fascinated many: How did Jews become such a remarkably successful minority in the modern western world? Eisen argues that Jews achieved such success because they were unusually well-prepared for it by their religion--in particular, Rabbinic Judaism, or the Judaism of the rabbis. Rooted in the Talmud, this form of Judaism instilled in Jews key values that paved the way for success in modern western society: autonomy, freedom of thought, worldliness, and education. The book carefully analyses the evolution of these four values over the past two thousand years in order to demonstrate that they had a longer and richer history in Jewish culture than in western culture. The book thus disputes the common assumption that Rabbinic Judaism was always an obstacle to Jews becoming modern. It demonstrates that while modern Jews rejected aspects of Rabbinic Judaism, they also retained some of its values, and these values in particular led to Jewish success. Written for a broad range of readers, Jews, Judaism, and Success provides unique insights on the meaning of success and how it is achieved in the modern world."--